Myo1f has an essential role in γδT intraepithelial lymphocyte adhesion and migration - Martínez-Vargas, Irving Ulises; Sánchez-Bello, Maria Elena; Miguel-Rodríguez, Carlos Emilio; Hernández-Cázares, Felipe; Santos-Argumedo, Leopoldo; Talamás-Rohana, Patricia (Frontiers in Immunology, 2023)
gdT intraepithelial lymphocyte represents up to 60% of the small intestine intraepithelial compartment. They are highly migrating cells and constantly interact with the epithelial cell layer and lamina propria cells. This migratory phenotype is related to the homeostasis of the small intestine, the control of bacterial and parasitic infections, and the epithelial shedding induced by LPS. Here, we demonstrate that Myo1f participates in the adhesion and migration of intraepithelial lymphocytes. Using long-tailed class I myosins KO mice, we identified the requirement of Myo1f for their migration to the small intestine intraepithelial compartment. The absence of Myo1f affects intraepithelial lymphocytes' homing due to reduced CCR9 and a4b7 surface expression. In vitro, we confirm that adhesion to integrin ligands and CCL25-dependent and independent migration of intraepithelial lymphocytes are Myo1f-dependent. Mechanistically, Myo1f deficiency prevents correct chemokine receptor and integrin polarization, leading to reduced tyrosine phosphorylation which could impact in signal transduction. Overall, we demonstrate that Myo1f has an essential role in the adhesion and migration in gdT intraepithelial lymphocytes.